The Use of ICT by EFL Teachers in Young Learner Classroom during Covid-19 Pandemic at A State School in Garut - Rahma Sakina; Muhammad Fikri Taufik; Shadam Hussaeni Handi Pratama (Ma'soem University, 2023)
Since the COVID-19 pandemic, online learning has become familiar to teachers and students, including in learning English for young learners. ICT is useful for student presentation learning media, such as Power Point, and learning to use Microsoft Word, Excel, and others. ICT is also useful as an independent learning medium such as E-Learning which can be done at school or at home. The various types of ICT have begun to be used by teachers and students of ELT media. The type of ICT that teachers use in English learning activities for young learners is software, including WhatsApp and YouTube. From this study, the researchers can find out the perceptions of teachers and parents regarding the advantages and disadvantages of using ICT in learning English for young learners. This study used the descriptive method to reveal the research problems. The interview is used to collect the data was conducted to English teachers. One of them, there are 32.2% who have not been able to fully operate ICT as a learning medium. This becomes a difficulty for young learners because they have not been able to master technology properly and correctly due to limited understanding.